A FRAMEWORK FOR EFFECTIVE E-COLLABORATION AND DIDACTICS ENHANCEMENT - YUSSIFF, ALIMATU-SAADIA (2016)
This thesis developed and validated a framework for effective e-collaboration and didactics enhancement. Three major problems identified at the onset of this research are; lack of comprehensive framework to serve as a commonly accepted framework for e-collaboration design and usage; gaps between constructivist online instructional design, teaching approaches and actual practices; and lack of social media use for collaboration